Phosphorylation of intracellular signalling molecules in peripheral blood cells from patients with psoriasis on originator or biosimilar infliximab5. (30th May 2018) - Aarebrot, A.K.; Solberg, S.M.; Davies, R.; Bader, L.I.; Holmes, T.D.; Gavasso, S.; Bryceson, Y.T.; Jonsson, R.; Sandvik, L.F.; Appel, S.
Summary: Background: Psoriasis vulgaris is a chronic, inflammatory skin disease characterized by a dysregulated immune response and it is associated with substantial systemic comorbidities. Biological drugs such as tumour necrosis factor (TNF)‐α inhibitors can ameliorate the disease but are expensive. Biosimilar drugs have the same amino‐acid sequence as the originator, but differences in manufacturing can affect biological activity, efficacy and tolerability. Objectives: To explore potential differences in intracellular phosphorylation of signalling molecules in peripheral blood cells from patients with psoriasis treated with the TNF‐α inhibitor infliximab compared with healthy controls, and to investigate if the phosphorylation pattern was influenced by switching from the originator infliximab to the biosimilar CT‐P13. Methods: By flow cytometry, we measured phosphorylation of nuclear factor kappa B, extracellular signal‐regulated kinase 1/2, p38 mitogen‐activated protein kinase and signal transducer and activator of transcription 3, before and after TNF‐α stimulation in monocytes and T, B, natural killer and CD3 +  CD56 + cells from 25 patients with psoriasis treated with infliximab and 19 healthy controls. Results: At inclusion, phosphorylation levels of peripheral blood mononuclear cells (PBMCs) were increased in patients with psoriasis compared with healthy controls, even though clinical remission had already been achieved. Phosphorylation levels declined in patients on both originator infliximab and biosimilar during continued treatment. No significant differences were detected between the two medications after 12 months. Conclusions: Patients with psoriasis on infliximab have higher activation levels of PBMCs than do healthy controls, possibly reflecting systemic inflammation. Switching from the originator infliximab to biosimilar CT‐P13 did not affect phosphorylation levels or clinical parameters, suggesting that CT‐P13 is a noninferior treatment alternative to the originator infliximab. Abstract : What's already known about this topic? The pathogenesis of psoriasis encompasses interactions between dendritic cells, T cells, keratinocytes and neutrophils. Certain cytokines, including tumour necrosis factor (TNF)‐α, from these cells activate intracellular signalling cascades, which can be measured using phospho flow cytometry. Infliximab and the biosimilar CT‐P13, both effective in psoriasis, act by binding TNF‐α. What does this study add? Peripheral blood mononuclear cells (PBMCs) from patients with psoriasis are more activated with higher intracellular signalling activity than PBMCs from healthy controls. This elevated activation level declines during infliximab treatment with no significant differences between originator and biosimilar infliximab. What is the translational message? Higher activation levels of PBMCs implies an ongoing systemic inflammation, possibly related to cardiovascular disease and obesity associated with psoriasis. Long‐term infliximab treatment may be beneficial in preventing such comorbidities. Switching from originator to biosimilar infliximab does not seem to influence intracellular signalling activity of PBMCs. Linked Comment:  Gjersvik. Br J Dermatol 2018;179 :247–248 . Plain language summary available online Respond to this article